2011
DOI: 10.1111/j.1756-185x.2011.01697.x
|View full text |Cite
|
Sign up to set email alerts
|

Different clinical features in patients with ankylosing spondylitis from southern and northern China

Abstract: Significant diagnostic delay and higher prevalence of HLA-B27 were found in southern AS patients. The prevalence of buttock pain and peripheral arthritis at disease onset in northern AS was more frequent than in southern AS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Delay in diagnosis of SpA has been described in women 5,9,10 and in both sexes 6,7,[11][12][13][14][15][16]20,26,27,29,30,32,33,35,38,39,40,44,45,46 , and although Bandinelli 23 observed less diagnostic delay in women than in men, in most of the papers where delay was compared between men and women, it was greater in women 8,17,18,19,21,22,28,31,34,37,41,42,43,47,48 . This implies that patients have had medically unsolved disorders for a long time, have continued searching for a diagnosis and treatment, or are being erroneously diagnosed and managed 49 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Delay in diagnosis of SpA has been described in women 5,9,10 and in both sexes 6,7,[11][12][13][14][15][16]20,26,27,29,30,32,33,35,38,39,40,44,45,46 , and although Bandinelli 23 observed less diagnostic delay in women than in men, in most of the papers where delay was compared between men and women, it was greater in women 8,17,18,19,21,22,28,31,34,37,41,42,43,47,48 . This implies that patients have had medically unsolved disorders for a long time, have continued searching for a diagnosis and treatment, or are being erroneously diagnosed and managed 49 .…”
Section: Discussionmentioning
confidence: 99%
“…men and women, means for men and women, and statistical significance) were calculated assuming similar variances for men and women. One of the studies 22 gave data for 4 subgroups that formed 4 different samples and these were included in the metaanalysis (southern China with juvenile AS, southern China with adult AS, northern China with juvenile AS, and northern China with adult AS).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…AS is a chronic autoimmune disease characterized by axial skeleton arthritis and enthesitis. [14,15] Although the pathogenesis of AS is not yet fully elucidated, an increasing number of studies have revealed an association between AS and the gut microbiome, [16,17] which plays an important role in the development of the immune system. [18,19] Several recent studies have also indicated a close relationship between food allergy and the intestinal microbiome.…”
Section: Introductionmentioning
confidence: 99%